SCIENTIFIC LITERACY SKILL PESERTA DIDIK DENGAN MODEL PEMBELAJARAN FREE INQUIRY PADA MATERI KEANEKARAGAMAN HAYATI - Santika, Wulan Puja; Suharsono, Suharsono; Badriah, Liah (Florea : Jurnal Biologi dan Pembelajarannya, 2020)
The purpose of this study was to determine the effect of the free inquiry learning model on scientific literacy skills of students on biodiversity material. This research was conducted in July to October 2019. The research method used true experimental with a population of all classes X SMA Negeri 6 Tasikmalaya as many as 7 classes with a total of 248 students. The samples used were 2 classes taken by cluster random sampling, namely class X MIPA-5 as a control class and class X MIPA-6 as an experimental class. The research instrument was in the form of a scientific literacy skill test in the form of multiple choices on biodiversity material, amounting to 48 questions. The data analysis technique used is the parametric statistical test (t test). 2 Based on the results of the study it can be concluded that there is an influence of the free inquiry learning model on the scientific literacy skills of students on biodiversity material in class X SMA Negeri 6 Tasikmalaya in the academic year 2019/2020.